Advice of Students of Teacher Training at Master Level on Studying at Home: Helyesnek vélt tanulási szokások (Training and Practice : Journal of Educational Sciences, 2016)
Nowadays one of the most important tasks of the teachers is to teach their students how to study. In addition they also have an important role in developing studying habits.In this research 200 teachers were asked who currently study teacher training at master level about their suggestions and advice on studying at home. They already work in various primary and secondary schools. While analysing these suggestions we try to answer the question, whether teachers have the same point of view on which habits are considered effective. Results suggest that the features of the given subject are key factors in this respect.